Staff perceptions of using outcome measures in stroke rehabilitation. (May 2013) - Burton, Louisa-Jane; Tyson, Sarah; McGovern, Alison
<x xml:space="preserve">Abstract</x> Purpose: The use of standardised outcome measures is an integral part of stroke rehabilitation and is widely recommended as good practice. However, little is known about how measures are actually used or their impact. This study aimed to identify current clinical practice; how healthcare professionals working in stroke rehabilitation use outcome measures and their perceptions of the benefits and barriers to use. Method: Eighty-four Health Care Professionals and 12 service managers and commissioners working in stroke services across a large UK county were surveyed by postal questionnaire. Results: Ninety-six percent of clinical respondents used at least one measure, however, less than half used measures regularly during a patient's stay. The mean number of tools used was 3.2 (SD = 1.9). Eighty-one different tools were identified; 16 of which were unpublished and unvalidated. Perceived barriers in using outcome measures in day-to-day clinical practice included lack of resources (time and training) and lack of knowledge of appropriate measures. Benefits identified were to demonstrate the effectiveness of rehabilitation interventions and monitor patients' progress. Conclusions: Although the use of outcome measures is prevalent in clinical practice, there is little consistency in the tools utilised. The term "outcome measures" is used, but staff rarely used the measures at appropriate time points to formally assess and evaluate outcome. The term "measurement tool" more accurately reflects the purposes to which they were put and potential benefits. Further research to overcome the barriers in using standardised measurement tools and evaluate the impact of implementation on clinical practice is needed.